Trends in opioid prescribing in Estonia (2011‐2017) - Anneli Uusküla; Mait Raag; Katrin Kurvits; Ott Laius; Maia Uusküla; Kersti Oselin (Wiley, 2020)
Abstract Our objective was to examine the trends and variation in opioid prescribing in Estonia from 2011 to 2017. This retrospective cross‐sectional study is based on a nationwide prescription medicines database. We stratified the analysis by treatment indication (cancer vs noncancer pain). Between 2011 and 2017, annual opioid prescribing rates increased by 67% (from 82.9 to 138.6 prescriptions per 1000 population). The annual number of prescriptions per patient did not change substantially (from 2.94 in 2011 to 2.87 in 2017), and was higher among cancer patients (5.07 vs 2.67 annual prescriptions per cancer and noncancer patients, respectively, in 2017). The use of the most potent opioids (morphine, fentanyl) was higher in noncancer than in cancer patients. The use of prescription opioids is low, and raises concern about the potential undertreatment of cancer pain, in parallel with misuse of opioids for either noncancer pain or diversion.